Developing Model of Charismatic Leadership to Small School Administrators - Khongsankham, Watchara; Ruangsuwan, Chayakan; Pollaharn, Chumnian (Journal for Developing the Social and Community, 2022)
The purpose attempts to study factors of charismatic leadership, developing model of charismatic leadership, and study affecting the used to model of charismatic leadership. A mixed method research via action research to study with 3 schools, by key informant including directors and teachers of 27 persons, and the sample of 150 persons. The collections to involved synthesizing documentary, visit study, interview questionnaire, and questionnaires to data analysis was analyzed by descriptive statistical analysis, frequency, percentage, mean and standard deviation. The results were to : 1) suitability level to charismatic leadership factors of high levels, 2) model of charismatic leadership such as 6 factor were to, (1) extremity vision (2) high personnel risk (3) idealized influence (4) inspirational motivation (5) intellectual stimulation and (6) individualized consideration. And (3) suitability and usefulness to model of most levels. Effecting use to the model from a training, by trainer groups have to knowledge, understanding to effectively of most levels.